Physiological, Nutritional, And Biochemical Responses Under Nickel Toxicity in Black Poplar (Populus nigra): Nickel toxicity in black poplar - Kulac, Semsettin; Cıkılı, Yakup; Samet, Halil; Filiz, Ertugrul (Journal of BioScience and Biotechnology, 2019)
Nickel (Ni) is an essential nutrient for plants and it has been identified as a component of a number of enzymes such as ureases. In this study, we have studied the long-term effects of nickel toxicity on black poplar (Populus nigra). The black poplars were exposed to Ni as NiSO4.6H2O (200, 400, or 800 µM) for 28 days by using complete randomized design with three replications. In this context, Ni accumulation and biomass, photosynthetic pigments analyses [chlorophyll a and b (Chl a and b), carotenoid (Car)], malondialdehyde (MDA) content, antioxidant enzyme activities [catalase (CAT) and ascorbate peroxidase (APX)], and metallic ion accumulations were investigated. Ni concentrations significantly increased in root, bark, and leaves in all Ni treatments. Also, reductions was determined significantly in the photosynthetic pigments (Chl a, Chl b, Chl a+b, and Car) at all Ni treatments. The MDA content, CAT and APX activities significantly increased compared the control plants. According to element analyses, the concentration of metallic ion accumulations [potassium (K), calcium (Ca), magnesium (Mg), sodium (Na), iron (Fe), zinc (Zn), manganese (Mn), and copper (Cu)] were affected by Ni exposures, suggesting that Ni toxicity adversely affects physiological activities in P. nigra.